2021
DOI: 10.1186/s12967-021-03081-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear HER3 expression improves the prognostic stratification of patients with HER1 positive advanced laryngeal squamous cell carcinoma

Abstract: Background Compared to the other members of human epidermal growth factor family receptors (HER), the role of HER3 has not been well defined in laryngeal cancer. The predictive and prognostic role of HER3 has been the focus of clinical attention but the research findings are contradictory, especially in laryngeal squamous cell carcinoma (LSCC). The variable localization of HER3 within cancer cells and the role of HER3 in primary and acquired resistance to HER1-targeted therapies remain unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Evidence in this respect comes from studies on laryngeal HNSCC in which ErbB3 was primarily observed in the nuclear compartment of tumor cells in association with variable cytoplasmic staining, and low expression levels of the receptor were associated with high proliferative indices, and with shorter relapse-free and overall survival (88,91). Further, EGFR-positive laryngeal tumors co-expressing nuclear ErbB3 had a better prognosis as compared to those that expressed EGFR without ErbB3 or in association with cytoplasmic ErbB3 (87). Moreover, based on the observation that ErbB3 was never expressed alone, but always co-expressed with ErbB2, both in the presence and absence of EGFR, the authors of these studies speculated that ErbB3 nuclear localization may play a favorable role by preventing the formation of ErbB heterodimers at the cell membrane and the ensuing activation of pro-tumoral downstream signaling pathways (87).…”
Section: Involvement Of Non-canonical Erbb Signaling In Hnsccmentioning
confidence: 99%
“…Evidence in this respect comes from studies on laryngeal HNSCC in which ErbB3 was primarily observed in the nuclear compartment of tumor cells in association with variable cytoplasmic staining, and low expression levels of the receptor were associated with high proliferative indices, and with shorter relapse-free and overall survival (88,91). Further, EGFR-positive laryngeal tumors co-expressing nuclear ErbB3 had a better prognosis as compared to those that expressed EGFR without ErbB3 or in association with cytoplasmic ErbB3 (87). Moreover, based on the observation that ErbB3 was never expressed alone, but always co-expressed with ErbB2, both in the presence and absence of EGFR, the authors of these studies speculated that ErbB3 nuclear localization may play a favorable role by preventing the formation of ErbB heterodimers at the cell membrane and the ensuing activation of pro-tumoral downstream signaling pathways (87).…”
Section: Involvement Of Non-canonical Erbb Signaling In Hnsccmentioning
confidence: 99%
“…In our previous studies, a close correlation was observed between the presence of high HER1 expression and a lower MFS; moreover, analysis of logarithmically transformed HER1 values showed that the risk of neck node relapse increased significantly with higher HER1 values, resulting in HER1 expression as an independent predictor of higher metastatic propensity [34,39]. The latter, in fact, is a prognostic factor of the clinical outcome [42], a biomarker of resistance to RT [45], and a target of cetuximab action [26,46].…”
Section: Discussionmentioning
confidence: 66%
“…Subsequently, lower progression-free survival (PFS) was documented in HNSCC overexpressing EGFR [40,41]. Overexpression of other receptor tyrosine kinases, including HER2, HER3, MPM7, and coexpression of all four HER family member (HER1, HER2, HER3, HER4) receptors, also may contribute to tumor resistance to EGFR-targeting agents [26,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations